Internal concentration as a better predictor of metal toxicity than the fractional coverage of metals on biotic ligand: Comparison of 3 modeling approaches. (7th July 2016) - Gao, Yongfei; Feng, Jianfeng; Zhu, Lin
Abstract: Modeling toxicity of metal mixtures poses unique challenges to the incorporation of bioavailability and metal speciation in metal exposures. Three models (models I, II, and III) were compared in the present study to predict and interpret the toxicity exerted by binary metal mixtures to zebrafish larvae, with the assumption of competition between metals based on the biotic ligand model and toxic potencies of individual metals. In addition, 3 models were developed by substituting binding constants ( fMBL ) for internal metal concentrations ( CM, int ) to directly delineate single‐metal and mixture effects on mortality of zebrafish larvae. The results indicated that the 3 developed models appeared to be much better ( p < 0.01) than 3 previous models at assessing the toxicity of different metal mixtures and showed 10% to 20% predictive improvement for each metal combination, with the toxic equivalency factor–based model II showing the best performance at quantifying metal mixture toxicity. The 3 developed models generally provided a reasonable framework and descriptions of bioavailability and additive (or nearly additive) toxicity for a number of binary metal mixtures. Environ Toxicol Chem 2016;35:2721–2733. © 2016 SETAC